GAMIFYING SENTENCE CONSTRUCTION: THE HIDE-AND-SEEK GAME AS AN ALTERNATIVE LEARNING STRATEGY - Nelvia Ibrahim (Jurnal Cakrawala Ilmiah, 2026)
Hide-and-Seek was one of the popular childhood games in Indonesia, and we can find it in every town in Indonesia. It involves one person “seeking” others who have hidden, fostering social skills, creativity, and problem-solving. Actually, Hide-and-Seek can be applied to arranging words into sentences for young learners, too. This game can be persuasive for young learners, especially for pupils who attend kindergarten through elementary school; this has been shown by some researchers.